(untitled) (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2018)
Common palm civet is a mamalia which often used to produce luwak coffee. Therefore health status of common palm civet is very important to be considered because force feeding of coffee can turn to stress condition. Glucose level, leukocyte profile and ratio N/L were often used as stress indicator. This study was aimed to determine glucose levels from blood of common palm civet, determine leukocyte profile and its deffirentiation also to calculate neutrophyl/limpocyte ratio from six common palm civet there were three group of observation, there were common palm civet coffe eaters and not coffe eaters. Blood samples were taken intracardially for further analyzed using manual blood method. Glucose levels of coffee eaters common palm civet was higher than common palm civet that was not coffee eaters. Stress index of coffee eaters common palm civet (0,516) was higher than not coffee eaters (0,463), but it was still in the normal range. Common palm civet that eat coffee continuosly can lead to oxidative stress condition.